Pre-emptive oral dexmethorphan reduces fentanyl-induced cough as well as immediate postoperative adrenocortico-tropic hormone and growth hormone level - Mukherjee, Avik (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Fentanyl-induced cough is not always benign and brief and can be remarkably troublesome, spasmodic, and explosive. Dextromethorphan, an opioid derivative with an antitussive action, may be effective in reducing the fentanyl-induced cough. Dextromethorphan, a N-methyl D aspartate receptor antagonist, may have some effect on diminishing the stress response to surgery. This study was undertaken to determine whether preoperative dextromethorphan could effectively attenuate its incidence, severity, and effect on postoperative stress hormone levels. MATERIALS AND METHODS: Three hundred and twenty patients of American society of anesthesiologists I-II, aged 18–60 years, undergoing elective laparoscopic cholecystectomy or appendicectomy were randomly allocated into two groups (Group C, control; Group D, dextromethorphan) consisting of 160 patients each. Patients in Group D received dextromethorphan 40 mg orally and in Group C received placebo tablets 60 minutes before induction of anesthesia. The incidence of cough was recorded for 1 minute after fentanyl injection and graded as none (0), mild (1–2), moderate (3–5), and severe (>5 cough). Blood samples were collected for estimation of stress hormone levels before surgery and again at 1 hour and 24 hours postoperatively and compared. The appearance of adverse reactions was recorded. RESULTS: The incidence of reflex fentanyl cough was lower in dextromethorphan group (3.9%) in comparison to placebo (59.8%). Five patients developed mild and one moderate cough in the dextromethorphan group. In the control group, 31 patients developed mild, 29 moderate, and 32 severe cough. The stress hormones were significantly higher at 1 hour and 24 hours postoperatively in both groups in comparison to its preoperative values. However, at 1 hour postoperatively, adrenocorticotropic hormone, epinephrine, and growth hormone values were significantly low in the dextromethorphan group (61.5 ± 21.1 pg/ ml, 142.1 ± 11.2 pg/ml, and 3.8 ± 0.7 ng/ml) relative to the control group (73.4 ± 21.9 pg/ml, 158.9 ± 17.9 pg/ml, and 4.2 ± 1.3 ng/ml), but changes became insignificant at 24 hours postoperatively. CONCLUSION: Preoperative oral dextromethorphan 40 mg decreased the incidence and severity of fentanyl induced cough and reduced the rise in stress hormones at 1 hour postoperatively.